Mary and the Trail of Tears : a Cherokee removal survival story - Rogers, Andrea L. (Girls survive., 2020)
It is June first and twelve-year-old Mary does not really understand what is happening: she does not understand the hatred and greed of the white men who are forcing her Cherokee family out of their home in New Echota, Georgia, capital of the Cherokee Nation, and trying to steal what few things they are allowed to take with them, she does not understand why a soldier killed her grandfather--and she certainly does not understand how she, her sister, and her mother, are going to survive the 1000 mile trip to the lands west of the Mississippi.